A História do Município e da Educação de Três Barras do Paraná - Bortolanza, Eliza (2022)
This research had the objective of investigating the history of the municipality and the education of Três Barras do Paraná. Through bibliographies, documents, and interviews, we sought to get closer and understand how that process occurred and how the changes succeeded. First, we ascertained how occurred the political transformations until the municipality emancipation, and we examined the struggles that happened about the territory occupation and the disputes for land tenure. Next, we aimed to understand the path of schooling, to verify how the first schools were created, and later, the extinction of most of them, the teaching methods, and the curriculum organization. Lastly, we will discuss the inclusion of the Historical Critical Pedagogy, that consists of a transforming pedagogical theory. We alluded how were conducted the first contacts, the study groups made in the municipality, the analysis of the socio-educational reality and the beginning of a more systematic activity of study, assuring the accomplishment of a process of a continued formation for the education professionals of all the municipal education network, in the intention of allowing the theoretical comprehension and a consequent practical activity in consonance with its theoretical-methodological conception. From the investigation and the concluded analysis, it was possible to determine that the history of education, organization and the social struggles belong together. In this regard this, it was also possible to comprehend that education can play a relevant role in the process of social transformation.